Effect of Second‐Order Spin–Orbit Coupling on the Interaction between Spin States in Spin‐Crossover Systems. Issue 20 (14th December 2017) - Sousa, Carmen; Domingo, Alex; de Graaf, Coen
Abstract: The second‐order spin–orbit coupling is evaluated in two transition‐metal complexes to establish the effect on the deactivation mechanism of the excited low‐spin state in systems that undergo spin transitions under the influence of light. We compare the standard perturbational approach to calculate the second‐order interaction with a variational strategy based on the effective Hamiltonian theory and show that the former one can only be applied in some special cases and even then gives results that largely overestimate the interaction. The combined effect of geometry distortions and second‐order spin–orbit coupling leads to sizeable interactions for states that are nearly uncoupled in the symmetric (average) structure of the complex. This opens the possibility of a direct deactivation from the singlet and triplet states of the metal‐to‐ligand charge‐transfer manifold to the final high‐spin state as suggested from the interpretation of experimental data but so far not supported by theoretical descriptions of the light‐induced spin crossover. Abstract : How does it work? Different calculation approaches were used to evaluate the influence of second‐order spin–orbit couplings on the deactivation mechanism of the excited low‐spin states in two transition‐metal complexes.